OCHRONA MIEJSC ŚWIĘTYCH W PRAWIE RZYMSKIM - Kamińska, Renata (Zeszyty Prawnicze, 2016)
PROTECTION OF HOLY PLACES IN ROMAN LAW SUMMARY Loca sacra enjoyed a broad scope of legal protection in Roman law. They were protected by interdicts, operis novi nuntiatio, and by government officials. The interdictive protection of holy places was analogous to the protection given to public places. One of the injunctions issued by the praetor to protect holy places was the loca sacra ne quid in loco sacro fiat prohibitory interdict, which imposed a ban on harmful activities on loca sacra premises, and prohibited offensive behaviour by private individuals in holy places. A second interdict for the protection of holy places was restitutory, whereby the praetor could order full restitution for offences committed in a holy place (quod in loco sacro religiosove factum est restituatur). The purpose of these two interdicts was to eliminate all obstacles to free and open access for all to holy places. A third interdict for the protection of holy places, interdictum quod vi aut clam, was restitutory as well. The creation of such a broad catalogue of legal measures including interdicts as administrative law remedies, testifies to the importance of holy places both in the public (including religious) and private life of the ancient Romans.